2006
DOI: 10.1002/jcc.20538
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical investigation of the excited states of OCLO radical, cation, and anion using the CASSCF/CASPT2 method

Abstract: Using the complete active space self-consistent field method with a large atomic natural orbital basis set, 10, 13, and 9 electronic states of the OClO radical, OClO(+) cation, and OClO(-) anion were calculated, respectively. Taking the further correlation effects into account, the second-order perturbation (CASPT2) calculations were carried out for the energetic calibration. The photoelectron spectroscopy of the OClO radical and OClO(-) anion were extensively studied in the both case of the adiabatic and vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…28 Since then, of course, remarkable progress in theory and computational technique for spectral analysis has been made. Among many others, [29][30][31][32][33][34][35][36] CASSCF and CASPT2 studies have been performed recently for several anionic species. 22,30,31,[34][35][36] But, even with recent advances in quantum chemistry theory, it is not easy to calculate dependable electronic excited states of radical anions compared with calculations for the closed-shell neutral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…28 Since then, of course, remarkable progress in theory and computational technique for spectral analysis has been made. Among many others, [29][30][31][32][33][34][35][36] CASSCF and CASPT2 studies have been performed recently for several anionic species. 22,30,31,[34][35][36] But, even with recent advances in quantum chemistry theory, it is not easy to calculate dependable electronic excited states of radical anions compared with calculations for the closed-shell neutral molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical calculations by Baluja et al 15 found no anion state in this energy range whereas Wei et al 16 reported a pair of B1 states in the energy range of 1 to 2 eV with an equilibrium bond length close to that of the neutral ground state. However, in this state they have found the equilibrium bond angle to be smaller indicating effective bending excitations from the Frank-Condon transition.…”
Section: Peak At 07 Evmentioning
confidence: 91%
“…The resonance obtained in these calculations around 3 eV is a single particle shape resonance of B1 symmetry. Wei et al 16 have reported an anion excited state near 1.5 eV with the smaller bond angle (112 0 ) and similar bond length as that of neutral ground state. Our results on OCl  validate this assignment.…”
Section: Ocl  Channelsmentioning
confidence: 94%
See 1 more Smart Citation
“…Grant et al 36 have included the OClO and ClOO species in a detailed ab initio investigation of the thermodynamic properties of halogen oxides based on coupled cluster theory and the correlated consistent basis sets of Dunning, obtaining accurate results for properties such as total atomization energies, geometries, frequencies, heats of formation, and bond dissociation energies. Additionally, Wei et al 37 have reported an extensive ab initio study of the spectroscopic properties of several excited states of the OClO radical as well as of its anion and cation, employing CASPT2/CASSCF methods with a large atomic natural orbital (ANO-L) basis set. They have given equilibrium structures, ionization potentials, detachment energies, and absorption spectra of up to 10, 13, and 9 electronic states of OClO, OClO + , and OClO − , respectively.…”
Section: Introductionmentioning
confidence: 99%